Integrasi Sistem Informasi Akademik dan E-Learning UIN Maulana Malik Ibrahim Malang berbasis Web Service REST - Ajib Hanani (SMARTICS Journal, 2020)
Universitas Islam Negeri (UIN) Maulana Malik Ibrahim of Malang has Academic Information System (SIAKAD) and E-Learning. They are used to manage the entire academic process in UIN of Malang. SIAKAD has been accessible via the internet and always updated. This is different from E-Learning, which is online and has not updated. The existing E-Learning data is entered manually and not scheduled automatically. In addition, the data entry are very complex, so that management becomes difficult. Data integration between SIAKAD and E-Learning should be created to solve the problem. The REST (REpresentational State Transfer) web service is a great choice of method to integrate many systems and databases. The result shows that data integration between SIAKAD and E-Learning in UIN of Malang can be created using REST web service. The SIAKAD data will be the same as the E-Learning data because the data is already synchronized. The data are data of students, lecturers, faculties, departements and courses. REST web services can be executed on a scheduling automatically using crontab application on Linux or FreeBSD operating system, so the data is no longer entered manually.